A STUDY OF FACTORS IN ASSESSING THE COMPETITIVE POSITION OF THE ENTERPRISE - Skorokhod, O. B. (Science and Transport Progress, 2007)
The theoretical scopes of consideration of different criteria of estimation of competition position of enterprise are represented. The results of empiric research with the target of the best cognition of conception of estimation of competition position of enterprise are analyzed.